Analisis Risiko Ketersediaan Energi yang Rendah dan Gangguan Makan pada Penari Elit Wanita di Sekolah Tari X di Jakarta, Indonesia: Hasil Penelitian - Sudarsono, Nani Cahyani; Lestari, Ria; Natasa, Yose (Cermin Dunia Kedokteran, 2024)
Due to their aesthetic demand and high training load, ballet dancers are often at risk of low energy availability (LEA), with or without eating disorders (ED). A prolonged state of LEA may alter physiological function and lead to other major health concerns. This study aims to analyze the risk of LEA and eating disorders in female elite dancers at X dance school in Jakarta. This descriptive cross-sectional design study was followed by 11 dancers. Risk of LEA was assessed using the low energy availability in females questionnaire (LEAF-Q), eating behaviors using the eating attitude test (EAT-26) questionnaire, and body composition using the bioelectrical impedance analysis (BIA) instrument. A total of 18.2% of dancers were at risk of LEA (LEAF-Q score ≥8) and no dancers were at risk of eating disorders. The most common characteristics of LEA are gastrointestinal dysfunction (90.9%), followed by menstrual disturbance (45.5%), and musculoskeletal injury (9.1%). Compared to the first study in Indonesia, this study showed lower proportion of dancers at risk of LEA and ED at X dance school in Jakarta. Despite a lower proportion, most dancers experienced other characteristics of LEA, thus prevention and health management are required to reduce further health issues.